Simulation of the operation of hydro plants in an electricity market using Agent-Based Models - José Carlos Sousa (2015)
The optimization and simulation of power systemscontinues to be an area of concern for electricity companies andresearchers worldwide namely considering the development ofelectricity markets and competition in the generation activityTherefore generation companies are devoting an increasingattention to market issues justifying the development of modelsto help them preparing bidding strategies to the day-aheadmarket. In this context, agent-based models have been reportedas a complement to optimization and equilibrium models whenthe problem is too complex to be analyzed by traditionalapproaches. This paper details an Agent-Based Model for anelectricity market considering a detailed modeling for hydrostations and presents some preliminary results taking theIberian Electricity Market as an example.